PENINGKATAN KETERAMPILAN BERBICARA MENGGUNAKAN MODEL THINK-PAIR-SHARE PADAKELAS XI IPA SMAN 1 TELUK KERAMAT - Wardania, Wardania; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by the problems faced by students when speaking. Weak ability of students to master the topic of talk, fluency, selection of appropriate diction, reduce the variety of regional languages and use Indonesian language, and appropriate intonation placement. The purpose of this study is the description of think-pair-share learning model (TPS) in improving speaking skills. This study specifically aims to describe the use of think-pair-share (TPS) learning models in improving students' ability in speaking according to the topic of conversation, fluency, diction, regional language variety and intonation in class XI IPA 2 of SMA N 1 Teluk Keramat in the academic year 2015/2016.The type of research is classroom action research (CAR) which is carried out in two cycles. The data of this study are planning, implementing, and speaking test result. The source of this research data is Indonesian language teachers and the students of XI IPA 2. Data are analyzed with descriptive qualitative. The results of data analysis, before the action is taken or at the pre-action stage, the average score of students is 67.5. The score in the first cycle after using think-pair-share learning model (TPS) increased to 72.2. The score in cycle II after using think-pair-share learning model (TPS) increased to 78.6. Based on the data from the students' speaking test results, from the pre-action stage, cycle I and cycle II, the total of increase score are 11.1. Keywords: Speaking, Think-Pair-Share (TPS), Action Research